ANALISIS PERAN DAN FUNGSI SISTEM PENGENDALIAN INTERN PEMERINTAH (SPIP/PP NO.60 TAHUN 2008) DALAM MEMINIMALISASI TINGKAT SALAH SAJI PENCATATAN AKUNTANSI KEUANGAN PEMERINTAH DAERAH - Mulyani, Pujianik; Suryawati, Rindah F (LPPM Universitas Terbuka, 2011)
This research examines the role and function of internal control system of government institutions in minimalizing accounting misstatement. Using qualitative descriptive research method, the object of this study incorporates the local government of Kabupaten Bojonegoro for the financial statements of year 2007-2009. The results shows that the increase quality of the Badan Pemeriksa Keuangan (BPK) opinion about financial statements of Kabupaten Bojonegoro were influenced by the improvement of internal control system function and optimalization of internal auditor role in every Satuan Kerja Perangkat Daerah (SKPD) in Kabupaten Bojonegoro. This research supports previous findings that internal control system has significant function and role in minimalizing accounting misstatement.